Microvascular Changes After Conbercept Intravitreal Injection of PDR With or Without Center-Involved Diabetic Macular Edema Analyzed by OCTA - Lin, Wei; Feng, Meng; Liu, Tingting; Wang, Qingxu; Wang, Wenqi; Xie, Xiao; Li, Wenhao; Guan, Jitian; Ma, Zhongyu; Liu, Tong; Zhou, Qingjun (Frontiers in Medicine, 2022)
Purpose To investigate the intravitreal injection of conbercept as a treatment strategy for proliferative diabetic retinopathy (PDR) with or without center-involved diabetic macular edema (CI-DME) and evaluate its effect on the microvascular changes in the eyes. Methods In this prospective study, 43 patients including 29 cases (56 eyes) in CI-DME with PDR patients, and 14 cases (26 eyes) in the non-center involving diabetic macular edema (NCI-DME) with PDR patients were involved in this study. The best corrected visual acuity (BCVA), central retinal thickness (CRT), foveolar avascular zone (FAZ), and macular capillary vessel density (VD) of the superficial retinal capillary plexus (SCP) and deep retinal capillary plexus (DCP) were assessed before and after conbercept treatments for 1, 3, or 6 months. Results The BCVA was significantly increased after conbercept treatment in the eyes of CI-DME patients. After 6 months of treatment with the conbercept, microvascular density of the inferior area in SCP and the central fovea area in DCP increased significantly, regardless of the central fovea involvement. The effect of the conbercept treatment on the VD of NCI-DME was higher than that of CI-DME. Then, after 6 months of treatment, the CRT of patients with CI-DME and NCI-DME were decreased significantly. Conclusions In this study, an intravitreal injection of conbercept significantly improved vision, alleviated macular edema in patients with DME. Conbercept treatment also altered the microvascular density in the retina.